2016
DOI: 10.1002/cphc.201600240
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic 5‐Substituted Uracils as Potential Radiosensitizers: A Density Functional Theory Study

Abstract: Although 5-bromo-2'-deoxyuridine (5BrdU) possesses significant radiosensitizing power in vitro, clinical studies do not confirm any advantages of radiotherapy employing 5BrdU. This situation calls for a continuous search for efficient radiosensitizers. Using the proposed mechanism of radiosensitization by 5BrdU, we propose a series of 5-substituted uracils, XYU, that should undergo efficient dissociative electron attachment. The DFT-calculated thermodynamic and kinetic data concerning the XYU degradations indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Hence, in the current work we synthesized 5-selenocyanato-2 0 -deoxyuridine (SeCNdU) and determined its susceptibility to be damaged by IR in aqueous solution. We also carried out another radiolytic studies for a modied 2 0 -deoxyuridine derivative that was indicated by our computational model, 11,19 namely for 5-triuoromethanesulfonyl-2 0 -deoxyuridine (OTfdU). The latter compound has been chosen since it is characterized by an exceptionally large thermodynamic stimulus for the DEA process, leading from the OTfdUc À radical anion to the 5-thio-2 0 -deoxyuridine radical.…”
mentioning
confidence: 99%
“…Hence, in the current work we synthesized 5-selenocyanato-2 0 -deoxyuridine (SeCNdU) and determined its susceptibility to be damaged by IR in aqueous solution. We also carried out another radiolytic studies for a modied 2 0 -deoxyuridine derivative that was indicated by our computational model, 11,19 namely for 5-triuoromethanesulfonyl-2 0 -deoxyuridine (OTfdU). The latter compound has been chosen since it is characterized by an exceptionally large thermodynamic stimulus for the DEA process, leading from the OTfdUc À radical anion to the 5-thio-2 0 -deoxyuridine radical.…”
mentioning
confidence: 99%
“…nucleosides with appropriately optimised features. Recently, we have undertaken attempts for rational designing of 5-substituted uracils prone to the dissociative electron attachment (DEA) process [18,19]. As a result, we proposed a series of 5-modified uracils with the DEA characteristics much better than those of BrdU [18,19] and the superior characteristics of some of them were confirmed in the photoelectron spectroscopy [18] and radiolytic studies [20,21].…”
Section: Introductionmentioning
confidence: 97%
“…The first stage of phosphorylation, the conversion of the nucleoside to the nucleoside monophosphate, is usually the rate-limiting step [22]. Hence, the favourable DEA profile [18,19] is necessary, but not a sufficient requirement for an efficient radiosensitising nucleoside. Taking into account that chemical synthesis is frequently not a trivial task and usually is a timeconsuming and costly process, it is difficult to overestimate access to a computational model that could tell, yet before the actual synthesis, if the proposed derivative is a good substrate for nucleoside kinase.…”
Section: Introductionmentioning
confidence: 99%
“…To answer these questions in the present paper we carry out a full QM investigation of the mechanism of α‐1,4‐glucan lyases including the final tautomerization process. This type of approach was already demonstrated to provide reliable results in the study of enzymatic mechanisms or biological/pharmaceutical processes . To this purpose, we use the M06‐2X functional and a QM model‐system built from the X‐ray crystal structure obtained by Rozeboom .…”
Section: Introductionmentioning
confidence: 99%
“…This type of approach was already demonstrated to provide reliable results in the study of enzymatic mechanisms or biological/pharmaceutical processes. [26][27][28][29][30][31][32][33][34][35] To this purpose, we use the M06-2X functional and a QM model-system built from the X-ray crystal structure obtained by Rozeboom. [22] This QM model-system (218 atoms) is rather large and includes all the aminoacidic residues that in principle can be responsible for important interactions.…”
Section: Introductionmentioning
confidence: 99%